Backlash in Attitudes after the Election of Extreme Political Parties - Magnus Carlsson; Gordon B. Dahl; Dan-Olof Rooth (Institute of Labor Economics (IZA), 2018)
Far-right and far-left parties by definition occupy the fringes of politics, with policy proposals outside the mainstream. This paper asks how public attitudes about such policies respond once an extreme party increases their political representation at the local level. We study attitudes towards the signature policies of two radical populist parties in Sweden, one from the right and one from the left, using panel data from 290 municipal election districts. To identify causal effects, we take advantage of large nonlinearities in the function which assigns council seats, comparing otherwise similar elections where a party either barely wins or loses an additional seat. We estimate that a one seat increase for the far-right, anti-immigration party decreases negative attitudes towards immigration by 4.1 percentage points, in opposition to the party's policy position. Likewise, when a far-left, anti-capitalist party politician gets elected, support for a six hour workday falls by 2.7 percentage points. Mirroring these attitudinal changes, the far-right and far-left parties have no incumbency advantage in the next election. Exploring possible mechanisms, we find evidence that when the anti-immigrant party wins a marginal seat, they experience higher levels of politician turnover before the next election and receive negative coverage in local newspapers. These findings demonstrate that political representation can cause an attitudinal backlash as fringe parties and their ideas are placed under closer scrutiny.
Keywords: D72; H70; 330; political backlash; far-right and far-left parties; public attitudes